2016
DOI: 10.1007/s00425-016-2496-4
|View full text |Cite
|
Sign up to set email alerts
|

Plant pressure sensitive adhesives: similar chemical properties in distantly related plant lineages

Abstract: A mixture of resins based on aliphatic esters and carboxylic acids occurs in distantly related genera Peperomia and Roridula , serving different functions as adhesion in seed dispersal and prey capture. According to mechanical characteristics, adhesive secretions on both leaves of the carnivorous flypaper Roridula gorgonias and epizoochorous fruits of Peperomia polystachya were expected to be similar. The chemical analysis of these adhesives turned out to be challenging because of the limited available mass fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The fruits (up to 3.5 mm in size) are small drupes consisting of a thin mesocarp, a stony endocarp and a hard testa ( Johnson, 1900 ; Fisher, 1914 ; Burger, 1971 ). As many Peperomia species show sticky secretions on the fruit surface ( Frenzke et al, 2016 ), epizoochorous dispersal has long been suggested by most (e.g., Dahlstedt, 1900 ; Ridley, 1930 ; Yuncker, 1958 ; Carlquist, 1967 ; Burger, 1971 ; Croat, 1978 ; Melcher et al, 2000 ), but not all authors ( Bradley, 2002 ). Although information on Peperomia dispersing animals is sparse, birds are considered as vectors by Ridley (1930) and Carlquist (1967) .…”
Section: Introductionmentioning
confidence: 99%
“…The fruits (up to 3.5 mm in size) are small drupes consisting of a thin mesocarp, a stony endocarp and a hard testa ( Johnson, 1900 ; Fisher, 1914 ; Burger, 1971 ). As many Peperomia species show sticky secretions on the fruit surface ( Frenzke et al, 2016 ), epizoochorous dispersal has long been suggested by most (e.g., Dahlstedt, 1900 ; Ridley, 1930 ; Yuncker, 1958 ; Carlquist, 1967 ; Burger, 1971 ; Croat, 1978 ; Melcher et al, 2000 ), but not all authors ( Bradley, 2002 ). Although information on Peperomia dispersing animals is sparse, birds are considered as vectors by Ridley (1930) and Carlquist (1967) .…”
Section: Introductionmentioning
confidence: 99%
“…The bands at 2929 cm -1 and at 1723 cm -1 are associated to C-H and C=O stretching vibrations, respectively. The band at 1723 cm -1 in combination with the bands at 3270 cm -1 and 1587 cm -1 could be accounted for carbonyl-bands of carboxylic acids [22]. Carboxylic acids have been found in the fruit of Cordia latifolia [23].…”
Section: Resultsmentioning
confidence: 96%
“…Nonetheless, full‐grown individuals of Weinmannia fagaroides and Polylepis quadrijuga were found in two of the plots of this cluster, together with some young individuals of Podocarpus oleifolia and Berberis glauca abundant in the lower canopy, and a dense cover of mosses and ferns, which suggests that some small “islands” of mature forest elements were able to persist within the disturbed, secondary forest matrix. Understory cluster 3 did not fit any previously described communities either, but the indicator species of this cluster are known to be either dispersed by birds, for example, Monnina aestuans (Romero, 2002) and Nertera granadensis (Vargas‐Ríos, 1997), or by small mammals or birds, for example, in the case of the sticky fruits of Peperomia (Frenzke et al., 2016). Possibly, this cluster represents a successional understory community mainly dispersed by animals, which prosper in previously disturbed areas, as suggested by the high people density within 5 km radius and relatively low mean tree biomass.…”
Section: Discussionmentioning
confidence: 93%